A cobalt(ii) spin-crossover compound with partially charged TCNQ radicals and an anomalous conducting behavior. Issue 2 (8th December 2015) - Zhang, Xuan; Wang, Zhao-Xi; Xie, Haomiao; Li, Ming-Xing; Woods, Toby J.; Dunbar, Kim R.
Abstract : A spin-crossover conductor with partially charged TCNQ exhibits a high room temperature conductivity and an anomaly in conductivity. Abstract : The bifunctional salt [Co(terpy)2 ](TCNQ)3 ·CH3 CN (terpy = 2, 2′;6′, 2′′-terpyridine, TCNQ = 7, 7, 8, 8-tetracyanoquino-dimethane) exhibits a high room temperature conductivity of 0.13 S cm −1 and an anomaly in conductivity at ∼190 K as evidenced by variable temperature structural, magnetic and conductivity studies. The anomaly in the conductivity at 190 K has been correlated with the temperature dependent structural breathing and Jahn–Teller distortion of the low spin state of the SCO units, as well as the charge fluctuations and supramolecular π-stacking interactions of partially charged TCNQ radicals. The modular synthetic approach leads to an accessible source of partially charged TCNQ radicals for the facile preparation of bifunctional molecular materials with high electrical conductivity.